1966
DOI: 10.1083/jcb.31.2.301
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Intracellular Osmiophilic Droplets

Abstract: Lipid solvent extraction of aldehyde-fixed hepatic tissue of rats caused disappcarancc of all intravascular and hepatoccllular osmiophilic droplets normally present, thus indicating their lipid content. Intramitochondrial dense granules and osmiophilic droplets in lysosomes also disappearcd after this treatment. Lipid solvents extracted 43.8 to 92.6% of the radioactivity from aldehyde-fixed rat liver with cla-labeled lipids. Only 0.7 to 5.8% of the radioactivity was extracted when the hepatic proteins were lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1968
1968
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(11 citation statements)
references
References 32 publications
(23 reference statements)
2
9
0
Order By: Relevance
“…It seems likely that soluble, unbound minerals localized within the matrix would be largely depleted during fixation and dehydration. Membrane-bound minerals, on the other hand, could be at least partially retained even though the formaldehyde-fixed membranes might well be stripped of most of their lipids during acetone dehydration (Ashworth et al, 1966). Rather uniquely, the ultrastructural appearance and macromolecular configuration of mitochondrial membranes appears to depend little, if at all, upon the presence of the lipid components (Fleischer et al, 1967).…”
Section: Al Sh Patterns From Control Mitochondriamentioning
confidence: 97%
See 3 more Smart Citations
“…It seems likely that soluble, unbound minerals localized within the matrix would be largely depleted during fixation and dehydration. Membrane-bound minerals, on the other hand, could be at least partially retained even though the formaldehyde-fixed membranes might well be stripped of most of their lipids during acetone dehydration (Ashworth et al, 1966). Rather uniquely, the ultrastructural appearance and macromolecular configuration of mitochondrial membranes appears to depend little, if at all, upon the presence of the lipid components (Fleischer et al, 1967).…”
Section: Al Sh Patterns From Control Mitochondriamentioning
confidence: 97%
“…This agrees with previously reported descriptions of aldehyde-fixed mitochondria (Sabatini et al, 1963;Andre and Marinozzi, 1965). Whether the granules are not present or are simply invisible in this preparation is not known, but the former seems most likely (Ashworth et al, 1966). After 30 min at 5000 or 600°C, sections of the control mitochondria are volatilized completely and leave no ash residue.…”
Section: Lin-fixed and Osmium-fixed Material-the Fate Of Normal Densementioning
confidence: 99%
See 2 more Smart Citations
“…Though the nature and function of the mitochondrial body still remains to be elucidated, it is generally accepted that they are lipid-rich (ASHWORTH et al, 1966) and it has also been presumed that they are involved in the transport of cations. ROUILLER (1960) andPEACHEY (1964) suggested that the normal matrix granules prime the accumulation of divalent cations.…”
Section: Discussionmentioning
confidence: 99%